Clinical and Radiological Characteristics of Pneumonia in COVID-19 Patients at First Admission of Dr. Soetomo General Academic Hospital, Surabaya, in June-August 2021 - Pradnyandari, Anak Agung Sagung Putri; Hasan, Helmia; Setiawati, Rosy; Effendi, Wiwin Is (Universitas Airlangga, 2025)
Highlights: This was the first study that described the radiological features of pneumonia in COVID-19 patients at first admission to Dr. Soetomo General Academic Hospital, Surabaya, during the Delta wave. This study presented the gastrointestinal symptoms of COVID-19 patients with pneumonia. Abstract Introduction: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) gave rise to the coronavirus disease (COVID-19) pandemic. Pneumonia in COVID-19 can cause acute respiratory distress syndrome (ARDS), which could lead to damage to end organs. This study aimed to describe the clinical and radiological profile of pneumonia in COVID-19 patients at first admission to the emergency department of Dr. Soetomo General Academic Hospital, Surabaya, in June-August 2021. Methods: This was a single-center, descriptive study of COVID-19 patients with pneumonia (n=193) at their first admission to the emergency department of Dr. Soetomo General Academic Hospital, Surabaya, from June to August 2021. The demographic data, pre-existing comorbidities, clinical signs and symptoms, and radiological findings were collected from the electronic medical record and analysed using the International Business Machines Corporation (IBM) Statistical Package for Social Sciences (SPSS) version 26. Results: Out of all the COVID-19 patients included in the study (n=193), most of them were 18-64 years old (86.0%), and the majority were males (50.8%). Of 193 patients, 51.3% had pre-existing comorbidities. Most patients (95.9%) experienced pulmonary symptoms, with shortness of breath being the most common. On chest radiograph, 60.1% patients showed consolidation with central and peripheral predominance (60.6%) and bilateral lung involvement (91.2%). Conclusion: This study presented a description of the clinical and radiological findings in COVID-19 patients with pneumonia. Most of which showed extensive lesions on chest radiograph along with dyspnea, which may suggest that most patients were suffering from late-stage and severe COVID-19 with pneumonia. To confirm this suggestion, further research is needed.